TINGKAT KESADARAN HUKUM MASYARAKAT TERHADAP KEPEMILIKAN SURAT IJIN MENGEMUDI (SIM) C DI KECAMATAN SEMAMPIR KOTA SURABAYA - Retno Multi Lestari; Rahmanu Wijaya (Kajian Moral dan Kewarganegaraan, 2021)
This study aims to describe the legal awareness of the community towards the ownership of a driving license (SIM) C in Semampir District, Surabaya City. Legal awareness is compliance with the law on a wide range of issues, including issues of knowledge, recognition, and respect for the law. This study uses Soekanto's theory of legal awareness. The research was conducted using a quantative approach with a descriptive design. The sample in this study amounted to 100 respondents using random sampling techniques. The data collection technique was carried out using a questionnaire. While the data analysis technique in this study is descriptive statistics with percentages. The results showed that the level of legal awareness of the community towards the ownership of a driving license (SIM) C in Semampir District, Surabaya City was in a low or poor percentage. Keywords: Legal Awareness, Driving License, Ownership.